Application of Raman spectroscopy for detecting the repairing behaviour of microcapsules in self-healing cementitious system - Mi, Tangwei (2024)
Evaluating the trigger mechanism of microcapsules is always an issue for self-healing cementitious materials, which could be potentially tackled by the application of Raman spectroscopy. In this paper, Raman spectroscopy was applied to tracing the repairing process in cementitious paste. Based upon the characterisation of the traditional UF/Epoxy microcapsule by Raman spectroscopy, the spectra of the microcapsule shell and core in cementitious matrix were identified and established. Furthermore, to improve the detection precision and efficiency, a newly designed microcapsule was developed in which the anatase was introduced in the microcapsule core to amplify the signal by around 90 times. Finally, the healing behaviour of the newly designed microcapsule was investigated by Raman mapping. The results clearly showed that Raman spectroscopy successfully detected the breakage of microcapsule due to the occurrence of cracking, which provides a promising approach to detecting the repairing behaviour of self-healing microcapsules in cementitious materials.